THE INFLUENCE OF THE HEAD MASTER TARNSFORMATIONAL LEADERSHIP STYLE TOWARD TEACHER'S WORK ETHICS IN THE AL-FARISI JUNIOR HIGH SCHOOL TAPOS TENJO BOGOR - Ahmad Farid; Arizqi Ihsan Pratama (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
Teacher work ethics are behaviors that exist in the teaching profession and are implemented in the teaching process, aiming to have norms and values of life in society that are related to the influence of the principal's transformational leadership style on teacher work ethics very closely related because in the implementation of the principal's duties as a leader , must have the right leadership style in order to improve the work ethics of teachers. Thus that the principal's transformational leadership style influences the work ethics of teachers. This research approach uses quantitative survey methods. The sample research in this study used a population sample, because given the limitations of the total population of 30 teachers. The research data collection technique was carried out using a questionnaire. The research procedure begins with the preparation of the grid, the preparation of the instrument, the testing, the results of the trial are tested for validity and reliability, the improvement of the instrument, then the instrument is used to retrieve data. Then the normality test, the linearity test, the inferential test of significance test and conclude the results of the study. The calculation results obtained by the regression equation Y = 18,001 + 1,264 X. And the results of regression testing using product moment regression, it can be seen that the price of regression (ryx) = 0.831 with a probability value (Sig. Fchange) = 0,000. Because the value of sig. Fchange <0.05, then the decision is H1: accepted and H0 rejected. It means significant. It can be concluded that the influence of the principal's transformational leadership style and significance on the teacher's work ethics. Simple correlation coefficient value of rxy = 0.831 and significance test 69.1% significance while the remaining 31.9% student discipline influenced by other variables.